Citizens Contacting the Police: The Dynamics of Police-Citizen Interactions During Two Voluntary Contacts - Toscano, Tracie L. (2005)
The thesis investigates two types of citizen initiated contacts with the police using data from the Bureau of Justice, “Contacts Between Police And The Public: Findings From The 1999 National Survey.” The two types of contacts examined are citizens asking for assistance from the police and citizens reporting neighborhood problems to the police. It was hypothesized that there are differences between citizens calling the police during these two contacts by demographic variables income, gender, age, and race. The descriptive findings were that people with higher income, females, between the ages of 25-44, and Whites call the police more than citizens with lower income, males, between the ages of 16-24 or over 65, and minority races. The findings suggest the importance of understanding police-citizen relations by demographic variables during voluntary contacts in order to strengthen police image and increase citizens’ satisfaction with the police